2007
DOI: 10.1002/adfm.200600632
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Study of a CaTiO3‐Based Mixed Conductor: Defects, Nanoscale Clusters, and Oxide‐Ion Migration

Abstract: Mixed oxide‐ion and electronic conductivity can be exploited in dense ceramic membranes for controlled oxygen separation as a means of producing pure oxygen or integrating with catalytic oxidation. Atomistic simulation has been used to probe the energetics of defects, dopant‐vacancy association, nanoscale cluster formation, and oxide‐ion transport in mixed‐conducting CaTiO3. The most favorable energetics for trivalent dopant substitution on the Ti site are found for Mn3+ and Sc3+. Dopant‐vacancy association is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…The calculated formation energies of the full Schottky, 2.19 eV for cubic CaTiO 3 and 2.66 eV for orthorhombic CaTiO 3 , are close to the previously reported value by G. C. Mather et al, of 2.49 eV, which was obtained for orthorhombic CaTiO 3 by the static lattice calculation. 17) As compared with the full Schottky, the CaO partial Schottky defect formation energy changed with equilibrium point. In the Ti-rich conditions (B, C, D and E), the CaO partial Schottky reaction for cubic CaTiO 3 was 1.21 eV, which is smaller than that in Ca-rich condition (A), 1.44 eV, and the CaO partial Schottky reaction is the most dominant defect species for the cubic phase in any equilibrium condition.…”
Section: Defect Formation Energies Of Neutral Isolated Vacancies and mentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated formation energies of the full Schottky, 2.19 eV for cubic CaTiO 3 and 2.66 eV for orthorhombic CaTiO 3 , are close to the previously reported value by G. C. Mather et al, of 2.49 eV, which was obtained for orthorhombic CaTiO 3 by the static lattice calculation. 17) As compared with the full Schottky, the CaO partial Schottky defect formation energy changed with equilibrium point. In the Ti-rich conditions (B, C, D and E), the CaO partial Schottky reaction for cubic CaTiO 3 was 1.21 eV, which is smaller than that in Ca-rich condition (A), 1.44 eV, and the CaO partial Schottky reaction is the most dominant defect species for the cubic phase in any equilibrium condition.…”
Section: Defect Formation Energies Of Neutral Isolated Vacancies and mentioning
confidence: 99%
“…Recently Mather et al reported the energetics of defects, dopant-vacancy association, and the nanoscale clusters formation in orthorhombic CaTiO 3 based on a static lattice calculation with empirical pair potentials. 17) First principles calculations of CaTiO 3 were also performed by Cockayne et al and Wang et al, but they were mainly focused on the dielectric constant, optical properties, and the surface structures. 18,19) In this study, the intrinsic defect formation energies in cubic and orthorhombic CaTiO 3 were calculated by a firstprinciples projector-augmented wave (PAW) method.…”
Section: Introductionmentioning
confidence: 99%
“…Rutile TiO 2 , with its relatively small ionicity and large dipole moments on anions, is a challenging system for developing an interatomic potential. Few of those we tried [28][29][30][31] could simultaneously provide the crystal structure, elastic properties, thermal expansion and phonon vibrational frequencies. The best results for phonon properties were obtained with the Buckingham potential (Model 3) developed by Mostoller and Wang (MW shell model) 31 .…”
Section: Molecular Dynamics Calculationsmentioning
confidence: 99%
“…Calcium titanate is an important mineral in many fields such as solid-state chemistry [22], biotechnology [23], and other applications in sensor devices and in solid oxide fuel cells [24]. Wu and co-workers at Sun Yat-Sen (Zhongshan) University synthesized CaTiO 3 crystals using a water-free poly(ethylene glycol) (PEG-200) solution [25].…”
Section: Perovskite Catiomentioning
confidence: 99%